KARAKTER VEGETATIF DAN GENERATIF BEBERAPA VARIETAS PADI (oryza sativa L.) TOLERAN ALUMINIUM - Wiwik Maya Sari; Eva Sartini Bayu; Syafrudin Ilyas Syafrudin Ilyas (Universitas Sumatera Utara, 2013)
Aluminium (Al) tolerant mechanism in rice has not been fully understood. The objective of thisresearch was to find the tolerant rice aluminum, and to study the vegetative and generativecharacters of Aluminum stress. Five days old of rice seedlings were growned on minimum culturesolution containing 15 ppm of Al for 72 hours and then transferred to non Al-treated culturesolution for 48 hours. The selected seedlings were measured based on Root Re-Growth (RRG)value. RRG value was determined based on after Al-stress. This research was held in theGreenhouse at Faculty of Agriculture, University of North Sumatera Utara, Medan, from May untilOctober 2012, using latin square design with treatment that were rice varieties: Hawarabunar,Ciherang, Inpari 1, Mekongga, Cibogo dan Cigelis. From the observations of RRG value obtainedthere were three tolerant rice varieties that were Hawarabunar, Ciherang and Mekongga, and threesensitive rice varieties that were Inpari 1, Cibogo dan Cigelis.Data analysis showed that varietieswith Al-treated were significantly different the plant height, the number of tillers, the vegetativestage, the number of productive tiller, the flower initation, the panicle length, the flag leaf length,the time of harvesting and the 1000 grain weight. Varieties were not significantly different thegenerative stage time, the number of empty grain per panicle, the number of panicle branches, andgrain weight per panicle.Keywords : rice, Al tolerant, Root Re-Growth